Oridonin Inhibits Tumor Growth in Glioma by Inducing Cell Cycle Arrest and Apoptosis - Zhang, X-H.; Liu, Y-X .; Jia, M.; Han, J-S.; Zhao, M.; Ji, S-P.; Li, A-M. (Cellular and Molecular Biology, 2014)
Glioma is the most common malignant intracranial tumors. Despite newly developed therapies, these treatments mainly target oncogenic signals, and unfortunately, fail to provide enough survival benefit in both human patients and mouse xenograft models, especially the first-generation therapies. Oridonin is purified from the Chinese herb Rabdosia rubescens and considered to exert extensive anti-cancer effects on human tumorigenesis. In this study, we systemically investigated the role of Oridonin in tumor growth and the underlying mechanisms in human glioma. We found that Oridonin inhibited cell proliferations in a dose- and time-dependent manner in both glioma U87 and U251 cells. Moreover, these anti-cancer effects were also confirmed in a mouse model bearing glioma. Furthermore, cell cycle arrest in S phase was observed in Oridonin-mediated growth inhibition by flow cytometry. Cell cycle arrest in S phase led to eventual cell apoptosis, as revealed by Hoechst 33342 staining and annexin V/PI double-staining. The cell apoptosis might be accomplished through a mitochondrial manner. In all, we were the first to our knowledge to report that Oridonin could exert anti-cancer effects on tumor growth in human glioma by inducing cell cycle arrest and eventual cell apoptosis. The identification of Oridonin as a critical mediator of glioma growth may potentiate Oridonin as a novel therapeutic strategies in glioma treatments.